Three-dimensional disordered alloy metamaterials: a new platform of structure-function integration - Xinxin Li; Liqiang Wang; Yang Lu (Materials Futures)
Metamaterials have garnered significant interest in recent years due to their unprecedented properties unattainable by natural substances and potential applications in various fields. In this review, we provide an in-depth analysis of a novel class of three-dimensional (3D) disordered alloy metamaterials, including metallic glasses and high/medium entropy alloys metamaterials, which offer a promising platform for the integration of structure and function. These materials are characterized by their unique including disordered atomic structures and alloy compositions modulation, enabling the manipulation of electromagnetic, thermal, and mechanical properties. We begin by discussing the underlying principles and synthesis methods of 3D disordered alloy metamaterials, followed by a comprehensive examination of their distinctive properties and potential applications in the realms of engineering, energy harvesting, and sensing. Furthermore, we delve into the existing challenges and future directions of this burgeoning field, encompassing aspects such as scalability, precision in fabrication, and the evolution of multi-functional materials. 3D disordered alloy metamaterials represent a promising avenue for the advancement of structure-function integration, with potential implications for a broad range of scientific and technological disciplines.